Design of novel dilute magnetic semiconductors by exhaustive first-principles calculations and scale-bridging simulations. (June 2022) - Shinya, Hikari; Kubota, Takaya; Tanaka, Yuichiro; Shirai, Masafumi
Abstract: Dilute magnetic semiconductors (DMSs) have attracted growing attention because of their potential advantages in semiconductor spintronics applications. However, as previous research has focused mostly on Mn-doped III–V semiconductors, little is known about other systems. Thus, to discover DMSs that are suitable for practical applications, an exhaustive search for zincblende-type DMSs was performed based on the Korringa–Kohn–Rostoker Green function method combined with the coherent potential approximation (KKR–CPA), and it was found that (Al, Cr)P and (Al, Cr)As maintained ferromagnetism at high temperatures. As the mean-field approximation significantly overestimates the Curie temperature by ignoring the magnetic percolation effect, a Monte Carlo simulation was performed to reproduce the experimental annealing procedure and estimate the Curie temperature using the random phase approximation, which considers the magnetic percolation effect. It was found that the Cr atoms in the AlP and AlAs host semiconductors gather together and form nanoclusters upon annealing based on attractive interactions. Furthermore, upon investigating how the annealing conditions affect the Curie temperature, it was found that the annealing temperature can modulate the density and size of the Cr nanoclusters, thereby controlling the Curie temperature. Moreover, it was deduced that the shapes of the nanoclusters could be changed by altering the dimensions of crystal growth. These results are essential to support materials manufacturing for next-generation semiconductor spintronics. Graphical abstract: Highlights: Promising DMSs were exhaustively searched based on first-principles calculations. (Al, Cr)P and (Al, Cr)As possess high Curie temperature. Annealing effect was investigated using scale-bridging simulations. Cr nanoclusters lead to the generation of an efficient ferromagnetic network. Magnetic property can be manipulated by density, size, and shape of Cr nanoclusters.